Advances in Biomedical Application of Nanocellulose-Based Materials: A Review - Yuan, Qi; Bian, Jing; Ma, Ming-Guo (Current Medicinal Chemistry, 2021)
Background: Recently, there has been increasing interest in nanomaterials processed using renewable and sustainable resources. Nanocellulose-based materials are of paramount value in the applications of biomedicine owing to their tailorable surface modification, favorable optical transparency, good hydrophilicity, excellent biocompatibility, and outstanding mechanical properties. Objective: In the review, the recent advancements of nanocellulose, including cellulose nanofibers (CNFs), cellulose nanocrystals (CNCs), and bacterial cellulose (BC), are summarized, which are promising for biomedical applications. Results: By discussing different forms (one-dimensional (1D), two-dimensional (2D), and three-dimensional (3D)), the superiority of the nanocellulose-based materials with different constructed structures will be clarified for various biomedical applications, such as biosensing, drug delivery, wound dressing, and tissue engineering. Conclusion: The challenges and prospects for the future development of nanocellulose- based materials in biomedical applications are also discussed at the end of the review.
Keywords: Biomedical applications